Assessing the Internalized Homophobia Scale for Gender Invariance. (1st October 2020) - Huynh, Kiet D.; Sheridan, Daniel J.; Lee, Debbiesiu L.
Abstract: The original and revised versions of the Internalized Homophobia Scale (IHP) were examined for gender invariance. The revised version was found to have a better fit, and passed the test of configural, metric, and scalar invariance. The revised version is recommended as a brief measure of internalized heterosexism.